PERANCANGAN APLIKASI UNTUK FREELANCER MENGGUNAKAN METODE WATERFALL BERBASIS WEBSITE - Farhan; Atang Susila (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
This research is motivated by a pandemic that has a negative impact on various aspects of people's lives, especially the current economy, online business is one solution to restore the current economy, but to carry out this online business requires special skills in the field, especially in the field of services, namely freelancers or freelancers, freelancers during the pandemic are one of the options that show an increasing trend at this time, for that the author took the initiative to create a system that brings together parties who are in need of freelancers and freelancers who have expertise in the IT or digital field, restrictions on this field, because the need for freelancers in that field is the greatest. In building this website, the researcher uses the waterfall method, where the initial stage of requirements is from the results of the needs analysis that comes from the results of the process of observing existing applications, then on the results of the design / system design there are several needs that are implemented. Then to the verification stage / system testing that has been implemented using the blackbox method, it can run as needed and is able to run on the web.